Characterization on hydrodynamic behavior in liquid‐containing gas‐solid fluidized bed reactor. Issue 4 (23rd July 2012) - Zhou, Yefeng; Ren, Congjing; Wang, Jingdai; Yang, Yongrong
<x xml:space="preserve">Abstract</x> In many industrial processes involving gas–solid fluidized bed rectors, the addition of a liquid phase significantly alters the hydrodynamics. To fully characterize the hydrodynamics in the fluidized bed, pressure and acoustic measuring techniques were applied to study the behavior of gas bubbles and particles. A camera was used to take pictures to verify the pressure and acoustic results. During the liquid‐addition process, the pressure technique captured the bubble size variation and bubble motion while the acoustic technique reflected particle motion and particle size growth. Hurst and V‐statistics analyses of acoustic emission were used for the first time to detect periodic behavior during the injection process. The new break formation and change trend of Vmax were used as the criteria to judge occurrence of abnormal fluidization states, such as agglomeration and gas channeling formation. These measurement techniques are beneficial in the elimination of adverse effects caused by the addition of liquid. © 2012 American Institute of Chemical Engineers AIChE J, 59: 1056–1065, 2013